Lessons From Pinocchio: Cues to Deception May Be Highly Exaggerated. (July 2019) - Luke, Timothy J.
Deception researchers widely acknowledge that cues to deception—observable behaviors that may differ between truthful and deceptive messages—tend to be weak. Nevertheless, several deception cues have been reported with unusually large effect sizes, and some researchers have advocated the use of such cues as tools for detecting deceit and assessing credibility in practical contexts. By examining data from empirical deception-cue research and using a series of Monte Carlo simulations, I demonstrate that many estimated effect sizes of deception cues may be greatly inflated by publication bias, small numbers of estimates, and low power. Indeed, simulations indicate the informational value of the present deception literature is quite low, such that it is not possible to determine whether any given effect is real or a false positive. I warn against the hazards of relying on potentially illusory cues to deception and offer some recommendations for improving the state of the science of deception.